Implementation of islamic education management in the admission of new students at SMK Teknindo Jaya - Devvi Diana Putri; Maemunah Sa’diyah; Nida Rafiqa Izzat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Acceptance of new students is crucial in the world of education. The goal is the quality of the school's educational institution. Acceptance of students begins with careful planning and implementation in such a way. This study uses a qualitative method, data collection is carried out directly through documents in the form of books and articles, then interviews are conducted with SMK Teknindo Jaya Depok and analysis using the Miles and Huberman technique. The results of the study obtained, SMK Teknindo opens admission of new students by referring to the policy of PERMENDIKBUD RI NO 1 of 2021. Planning is carried out carefully by the principal and all parties involved during the PPDB period. Acceptance of new students at SMK Teknindo Jaya is still conventional, but with good planning it will realize effective and efficient implementation. Implementation is carried out openly without any cheating and discrimination in it. At the end of the implementation, an evaluation is carried out as an assessment for the following year.